Silicone breast implant rupture from pectoralis muscle contraction causing IGA Nephropathy: a case report - Mahno, Noor Ezmas; Abdullah, Norlia; Aziz, Suraya; Wan Md Adnan, Wan Ahmad Hafiz; Lai, Meng Looi (Frontiers Media S.A., 2022)
A 34-year-old woman who was diagnosed with a left breast carcinoma underwent breast conserving surgery and axillary dissection. This was followed with adjuvant breast irradiation and endocrine therapy. She had a local recurrence in the breast 7 years later. She underwent a left nipple sparing mastectomy and submuscular implant reconstruction. The silicone implant ruptured during an episode of strong pectoralis muscle contraction, 5 years postimplantation. MRI confirmed the rupture to be intracapsular and extracapsular. She declined implant replacement. She presented with painless hematuria 2.5 years after the rupture. A renal biopsy confirmed IgA nephropathy.